Analysis of User Satisfaction MELISA using End User Computing Satisfaction (EUCS) and Importance Performance Analysis (IPA) Methods: Analisis Kepuasan Pengguna MELISA menggunakan Metode End User Computing Satisfaction (EUCS) dan Importance Performance Analysis (IPA) - Ningrum, Puspita Westi Erlitiya; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
The Ministry of Education and Culture made an innovation by launching the Merdeka Belajar Kampus Merdeka or MBKM program to help students preparing the transformation. To succeed the program, UNESA built a digital service called UNESA MBKM Information System or "MELISA". MELISA has been used since 2022 and only conducted an evaluation in 2023 after which there were improvements by adding several features and changing some of its appearance. In this study, researchers measured the level of user satisfaction of MELISA using the End User Computing Satisfaction (EUCS) and Importance Performance Analysis (IPA) methods. The purpose of this study is to determine the level of user satisfaction of MELISA and to determine the aspects that need to be improved and maintained by MELISA. Data collection was carried out by distributing questionnaires to UNESA students class of 2021. The number of samples used in this study were 153 respondents. The results of this study indicate that the level of user satisfaction based on the gap value obtained negative results on all indicators. Based on the results of the suitability level analysis, the result is 80.0% which includes <100%. Based on these two results, it indicates that MELISA's performance is still unable to meet the expectations of its users or still does not satisfy its users. In addition, based on the interpretation of the IPA diagram, indicators that are included in quadrant I, which means that they really need priority to make improvements, including user friendly (E1), transparency (C4), and suitability (F2).